Early dismissal in international commercial arbitration and its adoption by the United Nations Commission on International Trade Law - Orrantia Dworak, Fernando (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
Early dismissal is a procedural mechanism that allows a party to request the arbitral tribunal to decide one or more issues that are manifestly unfounded, at an initial or early stage of the proceedings, in order to terminate the proceedings or reduce the number of issues to be resolved in the final award. Early dismissal first appeared in investment arbitration and was later adopted by the main institutions of international commercial arbitration. The incorporation of this procedural instrument into the Notes on Organizing Arbitral Proceedings of the United Nations Commission on International Trade Law points towards its consolidation in international commercial arbitration.
Keywords: International comercial arbitration; early dismissal; Notes on Organizing Arbitral Proceedings; United Nations Commission on International Trade Law